Visual Branding Kupiah Meukutop 4.0: Blockchain untuk Pelestarian Warisan Budaya dan Penguatan Ekonomi Kreatif Pidie - Italina, Cut; Nofiana S; Setiawati, Cut Lilis; Ghifari, Muhammaad; Isnaini, Teuku; Amelia, Irza; Rahmayanti, Desi; Maryanti (Yayasan Sagita Akademia Maju, 2026)
The community service program “Visual Branding Kupiah Meukutop 4.0: Blockchain for Cultural Heritage Preservation and Strengthening the Creative Economy of Pidie” is motivated by the weak visual identity, limited digital promotion, and the absence of authentication systems for Kupiah Meukutop, a cultural heritage craft of Aceh. This program aims to enhance artisans’ capacity through the development of modern visual branding rooted in local wisdom and the integration of blockchain technology for product authenticity tracking. The implementation methods include needs assessment, training in visual design and digital marketing, development of a QR-based blockchain traceability prototype, and assistance in applying the new branding system. The results demonstrate significant improvement in artisans’ digital skills, the creation of new logos and packaging, initial blockchain implementation on 20 products, and increased online promotional activities. Overall, the program effectively contributes to cultural heritage preservation and enhances the competitiveness of Kupiah Meukutop within the regional creative economy sector.